Successful paediatric ABO incompatible renal transplantation with quadruple immunosuppression and B lymphocyte depletion. (29th September 2015) - Marks, SD; Sebire, NJ; Bradley, S; Wright, E; Mamode, N
Abstract : Aims: ABO incompatible renal transplantation has been reported as a successful form of renal replacement therapy in children and adults. Antibody removal is required with options of B lymphocyte depletion with splenectomy, plasma exchange, double filtration plasmapheresis or immunoadsorption. Methods: To report the successful outcome of ABO incompatible renal transplantation using quadruple immunosuppression (basiliximab at days 0 and 4, mycophenolate mofetil and tacrolimus from one week pretransplantation and corticosteroids) with only B lymphocyte depletion (intravenous rituximab 375 mg/m 2 at one month pretransplantation). A 14-year-old young man received a living related renal transplantation from his mother for end-stage renal failure (ESRF) on haemodialysis for steroid resistant nephrotic syndrome due to focal and segmental glomerulosclerosis (FSGS) who had a living related renal transplant from his father 18 months previously, which had failed due to a vascular event. Results: The recipient and donor (mother) blood groups were A and B Rhesus positive, respectively, with anti-B titres of one in four rising to one in eight pretransplantation. His renal transplant was performed successfully without further antibody removal or surgical complications and immediate renal allograft function. Three months posttransplant his renal function has stabilised with a plasma creatinine of 114μmol/l giving an estimated glomerular filtration rate of 62 ml/min/1.73 m 2 . He does not have clinical evidence of recurrent FSGS posttransplantation (normal serum albumin levels without albuminuria) with negative anti-B titres and donor specific antibodies and no evidence of EBV, BK or CMV viraemia (having required oral valganciclovir as CMV mismatch). He had a normal transplant renal biopsy at ten days post-transplant without evidence of acute rejection and one focal segmental sclerotic lesion seen on protocol biopsy at three months. Conclusion: In view of the reported success of ABO incompatible renal transplantation, clinicians must consider this option in ESRF patients whose parents have been excluded as living donors in view of ABO blood group incompatibility.